KARYA MUSIK LUNGUN: INTERPRETASI VOKAL ANDUNG BATAK TOBA DALAM KONSEP MUSIK KAMAR - Simanjuntak, Yessica Yosia Virginia (Institut Seni Indonesia (ISI) Surakarta, 2024)
Lungun is a musical work inspired by a tradition in the death ceremony of the Toba Batak people, called the andung tradition. Andung is a song of sadness that expresses one's feelings of grief for a loved one. Andung chanting is chanted by a pangandung (poet) using hata andung verses (Toba Batak fine literature) whose content tells the life history of someone who has died. In its current development, the andung tradition has shifted, and many cannot practice it because many younger generations can no longer speak hata andung, and andung singing which have been replacing with spiritual songs. The analysis of the andung tradition revealed distinct characteristics of the andung melody and the presentation of Gondang Sabangunan music for death ceremonies. The creation of the musical work Lungun aims to find out the musical form and its symbolic meaning. The method used is panca sthiti ngawi sani, which consist of five stages: (1) inspiration (ngawirasa), (2) exploration (ngawacak), (3) conception (ngarencana), (4) execution (ngawangun) and (4) production (ngabah). Lungun's musical work incorporates elements such as the Toba Batak scales, processed andung vocals, hata andung poems, rhythm processing, and Gondang Sabangunan playing techniques into chamber music performances. Lungun music has three parts: part I is mula-mula (beginning), part II is andung (vocal singing), and part III is poda (message). The symbolic meaning expressed in Lungun music refers to the values found in the Toba Batak community: the Dalihan Na Tolu Batak philosophy, the five levels of Toba Batak death, and the seven Toba Batak philosophies.